2017
DOI: 10.18632/oncotarget.17859
|View full text |Cite
|
Sign up to set email alerts
|

Heat-killed salmonella typhimurium (HKST) protects mice against radiation in TLR4-dependent manner

Abstract: It is urgently required to develop novel safe and effective radioprotectors to alleviate radiation damages. Recently, several toll like receptors (TLRs), including TLR2, TLR4, TLR5, TLR9, have been proved to exert protective effects against ionizing radiation. Due to different tissue-distribution and distinct functions of TLRs, we hypothesized that co-activation of multiple TLRs simultaneously may produce extensive and stronger radioprotective effects. In this study, we found the co-agonist of TLR2, TLR4 and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In previous immunological studies, it has been reported that HKST effectively activates TLR2 and TLR4, and activates TLR5 at high concentration with its flagellin . Our previous study found HKST significantly inhibited radiation‐induced cell apoptosis, increased cell survival and alleviated DNA damage, and we found that TLR4 is more significant for the radioprotective effects of HKST by using knockout mice and siRNA model, meanwhile, the protective effects of HKST is partially dependent on TLR2 . In this study, we demonstrated that HKST effectively mitigated radiation injury and inflammation in lung tissues.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…In previous immunological studies, it has been reported that HKST effectively activates TLR2 and TLR4, and activates TLR5 at high concentration with its flagellin . Our previous study found HKST significantly inhibited radiation‐induced cell apoptosis, increased cell survival and alleviated DNA damage, and we found that TLR4 is more significant for the radioprotective effects of HKST by using knockout mice and siRNA model, meanwhile, the protective effects of HKST is partially dependent on TLR2 . In this study, we demonstrated that HKST effectively mitigated radiation injury and inflammation in lung tissues.…”
Section: Introductionsupporting
confidence: 54%
“…The latest research showed that CBLB502, a TLR5 agonist derived from Salmonella flagellin , effectively protected mammalian haematopoietic and gastrointestinal systems from acute irradiation syndrome . Our previous studies have also proved that activation of TLR2 and TLR4 significantly protected mice and cultured cells against ionizing radiation. However, the expression levels of different TLRs in distinct cells in lung tissues are greatly varied, and different types of TLRs initiate different downstream pathways, so we assume that the activation of multiple TLRs can exert a broader radiation protection effect in RILI.…”
Section: Introductionmentioning
confidence: 87%
“…Previous study have shown that the pretreatment with attenuated Salmonwlla typhimurium could induce protective cell-mediated immunity or facilitate the conversion of immunosuppressive myeloid-derived suppressor cells into TNF-α-secreting neutrophil-like myeloid cells thereby protecting mice against malaria or tumor [17,18]. In our preliminary work, damages on bone marrow, spleen and testis which were induced by γ-irradiation could be signi cantly eased by the pretreatment of HKST [19]. However, the radio-protective effects of HKST on small intestine has remained unclear.…”
Section: Introductionmentioning
confidence: 65%
“…Currently, several TLRs ligands have been proved to exert radioprotective effects, for example, CBLB502 for TLR5, CpG-ODN for TLR9, LPS for TLR4 and CBLB613 for TLR2/6 etc. Our group also demonstrated that Heat-Killed Salmonella typhimurium and Heat-Killed Mycobacterium tuberculosis protected mice against radiation through TLR signaling pathways [ 16 , 17 ]. These findings shed new lights for application of TLR ligand in clinics.…”
Section: Discussionmentioning
confidence: 99%